Optimization and fabrication of Load carrying device design using ANSYS DO Module. Issue 1 (1st October 2022) - Gangwar, Ansh; Srivastava, Sambhrant; Kumar, Adesh; Umar, Md
Abstract: Simulation technique is one of the advanced techniques in Finite Element Method. It is used as one of the tools for designing and analysis of any structure. Load carrying device is important for labors in construction works, cargo carrying etc. because the most efficient and cheap design can help them from hazardous and poisonous environment. Different load carrying device are available but their optimization regarding the load is still a challenge. In this work we have taken reference of female labors carrying load on their head like, bricks, cement, concrete on construction sites. To achieve this, a parametric design is done in ANSYS software and optimize the shape and mass of load carrying device using DO module. Then using guadua bamboo a load carrying device is made and its weight is measured. Load carrying device suitability is checked by carrying bricks on the construction site.